Virtually Hosted Hackathons for Design Research: Lessons Learned from the International Design Engineering Annual (IDEA) Challenge 2021. (May 2022) - Goudswaard, M.; Kent, L.; Giunta, L.; Gopsill, J.; Snider, C.; Valjak, F.; Christensen, K. A.; Felton, H.; Ege, D. N.; Real, R. M.; Cox, C.; Horvat, N.; et al.
Abstract: This paper provides an overview and appraisal of the International Design Engineering Annual (IDEA) challenge - a virtually hosted design hackathon run with the aim of generating a design research dataset that can provide insights into design activities at virtually hosted hackathons. The resulting dataset consists of 200+ prototypes with over 1300 connections providing insights into the products, processes and people involved in the design process. The paper also provides recommendations for future deployments of virtual hackathons for design research.